Flexible sorption enhanced gasification (SEG) of biomass for the production of synthetic natural gas (SNG) and liquid biofuels: Process assessment of stand-alone and power-to-gas plant schemes for SNG production. (15th October 2016) - Martínez, I.; Romano, M.C.
Abstract: A flexible sorption enhanced gasification (SEG) process is assessed in this work, where CaO-based material circulating between gasifier and combustor reactors is adjusted for fulfilling the syngas composition requirements according to the downstream fuel synthesis process. A case study of a synthetic natural gas (SNG) production plant based on this SEG process is presented, which has been analysed under different conditions of gasification temperature or solid circulation. A possible integration of this plant with an electrolysis system for power-to-gas application for balancing the electric grid is also proposed and assessed. SNG production efficiencies as high as 62% (LHV-based) have been found for the production of SNG with final CH4 content of 98%. Excess energy recovered from the process streams can be used for producing electricity in a steam turbine, covering the electric demand in the plant. If credits associated to electricity production are considered, equivalent SNG production efficiencies higher than 70% have been calculated. Efficiencies reported in this work are in the upper limit of the range found in the literature for non-SEG concepts, which require an intermediate conditioning step of WGS and CO2 removal. When coupled with an electrolyser, power-to-gas efficiencies of about 60% have been calculated, in line with stand-alone power to gas methanation systems. Highlights: Flexible sorption enhanced gasification (SEG) assessed by process simulation. A case study for synthetic natural gas (SNG) production is presented. Integration of SEG-SNG process with a power-to-gas plant is assessed. Overall SNG production efficiencies higher than 70% have been calculated. Power-to-gas efficiencies of about 60% when integrated with electrolysis.